Development and validation of a scale for identification of quality attributes of agri-food products in short chains. Issue 111 (May 2020) - Rossi Scalco, Andréa; Miller Devós Ganga, Gilberto; Cristina De Oliveira, Sandra; Baker, Gregory
Highlights: Focuses on intensive production systems to traditional markets. There is a need for new tools to assess consumer perceptions. Develops an instrument for understanding consumer behavior in agri-food short chains. Price is not the most relevant factor to consumers in agri-food short chains. Rooting, trust, and place are attributes most valued by the consumers. Abstract: The quality of the agri-food product, as well as the attributes that define it, has been developed for decades, where discussions around the theme turned to questions related to the standardization of attributes. It should be noted that the theoretical lines associated with the theme are derived from production systems models where production productivity and distribution on a global scale are the guiding principles of food production. Currently, there is greater demand for products coming from a model that contrasts with the global-scale production model, which emphasizes the aspects of standardization of products and processes. This new model of food consumption highlights specific characteristics of product quality related to the location and proximity to the producer. Discussions about product quality in this new model of production and consumption (agri-food short chains) are recent and need a theoretical and practical deepening, in view of the new demands of consumers for these products. This paper aims to present the development and validation of a scale with quality attributes from the consumer point of view applied specifically to food and beverage products characterized by agri-food short chains. Items were generated (27 quality attributes) from an extensive theoretical review (quality conventions), subjected to face validation, and then used to collect data from 904 consumers in short food distribution channels in the Brazilian state of São Paulo. The data were analyzed through exploratory and confirmatory factor analysis, which resulted in a final scale composed of 20 quality attributes comprising, domestic, civic, regard, institutional, and market conventions.